Barreras de acceso a servicios de salud mental en el corregimiento de Morelia Roldanillo (V) (2024)
This research thesis focuses on understanding how barriers to access mental health services are configured and overcome in rural areas of the Municipality of Roldanillo. Firstly, the introduction presents the context of mental health in rural settings, highlighting the relevance of addressing this topic. The background examines the existing literature on barriers to access to mental health in rural areas, providing a theoretical framework for the study. The main objective is to analyze the approach to mental health in the rural areas of Roldanillo, identifying specific access barriers and evaluating the impact of the urban disciplinary tradition in Psychology in this context. The research adopts a quantitative approach, using a scoping review instrument and a survey applied to 20 people from the town of Morelia to collect data. The results of this study are expected to provide valuable information about the barriers that rural communities face in accessing mental health care, as well as possible strategies to overcome them. This analysis will contribute to the design of more effective and equitable policies and programs for mental health in rural settings.